Preference of media politics and beginner voter trust in Surakarta - Erwin Kartinawati; Andrik Purwasito (Journal of Social Studies (JSS), 2021)
The Indonesian Presidential Elections of 2014 and 2019 indicated the behavioral changes in mass media, especially that of private television. The involvement of media owners in the political arena can influence the content of most journalistic broadcasts. Therefore, this study aims to determine the perception of student voters in Surakarta on media houses with political preferences. This might be because the media owner is actively supporting a political party or a particular candidate. Furthermore, if the media is under the influence of politics, how can voters have trust in the information dissipated, especially during elections. The data obtained for this study was through the distribution of questionnaires to college students aged 17-25 years that are voting for the first time. Most of the respondents stated that their political choices are not necessarily influenced by the media. The belief in the media is not directly related to political preferences but depends on the content or what is conveyed to the public. However, the involvement of media owners in politics also undermines public trust in the content of the media, especially about political news.